New and explanation records to the brushfoots (Papilionoidea: Nymphalidae) from Guatemala - Salinas–Gutiérrez, José Luis (Instituto de Ecología, A.C., 2013)
I present two species and five subspecies as new records for Guatemala, as well as confirmed the presence of three subspecies. And I mention some issues about taxonomic and distributional information. Also, I mention the data of one Ithomiini (clearwings), and one Morphini (morphos), as probable subspecies with distribution in Guatemala.